Em teoria - Sergio Augusto Medeiros (2023)
The doctoral thesis is an academic-scientific genre that follows specific methodologies, which are shaped by the thematic approach of the specialized field and presents evidence through the analysis of hypotheses. Comprising various areas of knowledge, methods, and processes related to the development of descriptions, such as representations of subjects, languages, and codes, the present thesis aims to describe and formulate the hypothesis that gave rise to a scientific theory, employing methodological rules and procedures to ensure the validity and consistency of the results obtained. The scientific theory is a structure that aims to describe, predict, and control phenomena through empirical evidence, laws, hypotheses, models, and concepts. To investigate a specific research problem, a thematic and systematic approach was adopted, following stages of observation, hypothesis formulation, testing, analysis of results, and validation. By combining thesis formatting with metaphors, the editing seeks to simulate the very concept of a thesis to identify the hierarchies and conventions of the scientific method.